2021
DOI: 10.1016/j.bbih.2021.100327
|View full text |Cite
|
Sign up to set email alerts
|

Short review: The impact of sex on neuroimmune and cognitive outcomes after traumatic brain injury

Karen Krukowski

Abstract: Traumatic brain injury (TBI) is an ever growing health concern, with cases increasing in both the US and the world at large. With the improvement of emergency medicine in recent decades, survival from TBI has become more common place, and thus individuals are coping with long-term deleterious outcomes from trauma as a result. Such outcomes include altered cognitive (memory loss/executive function), social (isolation tendencies), and behavioral (risk-taking behavior/anxiety) function. Researchers use preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Here we demonstrate robust blast-induced changes in serum and brain cytokine levels that display similar and disparate patterns in male vs. female mice. In line with these results, models of single moderate to severe impact TBI have demonstrated disparate inflammatory outcomes in male vs. female mice acutely following injury (Bromberg et al, 2020;Doran et al, 2019;Krukowski, 2021;Krukowski et al, 2020;Späni et al, 2018;Villapol et al, 2017). Likewise, a recent study using a single mild blast exposure with body shielding reported worse acute and sub-acute neuroinflammatory and BBB outcomes in male vs. female rats (Hubbard et al, 2022).…”
Section: Discussionmentioning
confidence: 82%
“…Here we demonstrate robust blast-induced changes in serum and brain cytokine levels that display similar and disparate patterns in male vs. female mice. In line with these results, models of single moderate to severe impact TBI have demonstrated disparate inflammatory outcomes in male vs. female mice acutely following injury (Bromberg et al, 2020;Doran et al, 2019;Krukowski, 2021;Krukowski et al, 2020;Späni et al, 2018;Villapol et al, 2017). Likewise, a recent study using a single mild blast exposure with body shielding reported worse acute and sub-acute neuroinflammatory and BBB outcomes in male vs. female rats (Hubbard et al, 2022).…”
Section: Discussionmentioning
confidence: 82%
“…More recently, mTBI effects and long-term sequelae are being extensively studied, such as noise sensitivity [12], insomnia [13], cognitive impairment [14], visual field defects [15], changes in White Matter (WM) Fractional Anisotropy (FA) [16], among many others. However, most of these studies regarding mTBI lack sex-specific data, even though distinct effects on women and men are often reported in the literature [17,18].…”
Section: Introductionmentioning
confidence: 99%
“… Krukowski (2021) summarizes evidence for sex differences in models for traumatic brain injury (TBI) and space radiation. Overall, it is revealed that neuroimmune alterations, like microglial responses, appear to be more severe in male than female animals or even absent in females exposed to space radiation.…”
Section: Introductionmentioning
confidence: 99%